Whataboutisms: The Good, the Bad and the Ugly - Bowell, Tracy (Informal Logic, 2023)
The rhetorical function of whataboutism is to redirect attention from the specific case at hand. Although commonly used as a rhetorical move, whataboutisms can appear in arguments. These tend to be weak arguments and are often instances of the tu quoque fallacy or other fallacies of relevance. In what follows, I show that arguments involving a whataboutist move can take a wide variety of forms, and in some cases, they can occur in good arguments. I end by considering how whataboutist arguing in social justice contexts can be harmful to arguers and to the audiences for their arguments.